Analisis Akad Ijarah dan Peraturan Menteri Ketenagakerjaan No 6 Tahun 2020 tentang Penyelenggaraan Pemagangan di Dalam Negeri terhadap Tenaga Kerja Magang di CV Mekar Utama Computer - Maulydiani Utami Azzahra; Sandy Rizki Febriadi; Ira Siti Rohmah Maulida (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. This research is motivated by the rise of apprenticeship programs organized by various companies in Indonesia, opening up many opportunities to compete with each other and improve soft skills and hard skills to jump directly into the world of work. The work that should be the work of a worker is still done by the intern but the intern does not get his rights in the form of pocket money, occupational safety and health facilities while participating in the apprenticeship, this makes there is a discrepancy between the rights of the intern worker as stated in the regulation of the Minister of Manpower No. 6 of 2020 concerning the implementation of apprenticeships in the country. The purpose of this study is to find out how the rights, rights, and protection of interns are reviewed through the ijarah contract and the regulation of the Minister of Manpower no.6 of 2020. In this study, a type of qualitative method is used with a field research approach based on the reality that occurs in the field. The data sources of this research use primary data sources obtained directly by researchers in the field and secondary data sources are additional data sources that can be used as additional materials or supplements obtained from the Qur'an, Hadith, Ministerial Regulations, Articles, Journals and Books. The results of the study show that the internship workforce at CV. Mekar Utama Computer received legal protection in the form of job training before the apprenticeship process, the provision of sarongs, rest time, worship time, knowledge and certificates. Based on the analysis of the ijarah contract and the Regulation of the Minister of Manpower No.6 of 2020 concerning the implementation of apprenticeships in the country, there is a discrepancy between the rights of interns as stated in the Regulation of the Minister of Manpower No.6 of 2020 concerning the implementation of apprenticeships in the country, such as the absence of pocket money to the interns, but if viewed in terms of the ijarah contract, The agreement of this apprenticeship process has been fulfilled in its pillars. Abstrak. Penelitian ini dilatarbelakangi oleh Maraknya program pemagangan yang diselenggarakan oleh berbagai perusahaan di Indonesia membuka banyak peluang untuk saling bersaing dan meningkatkan soft skill maupun hard skill untuk terjun langsung ke dunia kerja. Pekerjaan yang seharusnya menjadi pekerjaan seorang pekerja tetap dikerjakan juga oleh peserta magang tetapi tenaga kerja magang tidak mendapatkan haknya berupa uang saku, fasilitas keselamatan dan kesehatan kerja selama mengikuti pemagangan, hal ini membuat adanya ketidaksesuaian antara hak tenaga kerja magang yang tertera pada peraturan Menteri ketenagakerjaan No.6 tahun 2020 tentang penyelenggaraan pemagangan di dalam negeri. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana hak hak dan perlindungan tenaga kerja magang bila ditinjau melalui akad ijarah dan peraturan Menteri ketenagakerjaan no.6 tahun 2020. Dalam penelitian ini menggunakan jenis metode kualitatif dengan pendekatan penelitian lapangan yang didasarkan dari realitas yang terjadi di lapangan. Sumber data penelitian ini menggunakan sumber data primer yang didapatkan secara langsung oleh peneliti di lapangan dan sumber data sekunder merupakan sumber data tambahan yang dapat dijadikan sebagai bahan tambahan atau pelengkap yang diperoleh dari Al-qur’an, Hadist, Peraturan Menteri, Artikel, Jurnal dan Buku. Hasil penelitian menunjukkan bahwa tenaga kerja magang pada perusahaan CV. Mekar Utama Computer mendapatkan perlindungan hukum berupa pelatihan kerja sebelum berjalannya proses pemagangan, diberikannya sarung, waktu istirahat, waktu beribadah, mendapatkan ilmu dan pemberian sertifikat. Berdasarkan analisis akad ijarah dan Peraturan Menteri Ketenagakerjaan No.6 Tahun 2020 tentang penyelenggaran pemagangan di dalam Negeri, terdapat ketidaksesuaian antara hak tenaga kerja magang yang tertera pada peraturan Menteri ketenagakerjaan No.6 tahun 2020 tentang penyelenggaraan pemagangan di dalam negeri, seperti tidak diberikannya uang saku kepada tenaga kerja magang, namun jika ditinjau dari segi akad ijarah, perjanjian proses pemagangan ini sudah terpenuhi rukun-rukunnya.